Experimental abrasion analysis of textile capacitive sensors - Martínez-Estrada, Marc; Ventura, Heura; Gil, Ignacio; Fernández-García, Raúl (Wydawnictwo Politechniki Łódzkiej, 2022)
This paper presents an experimental abrasion analysis of textile capacitive sensors based on Martindale test. The textile sensor is manufactured with a well-known woven technology where some yarns are replaced by electrical conductive yarn. Specifically, two types of conductive yarns were used to compare the abrasion behaviour respect to conventional fabrics and the impact of abrasion on sensors functionality. The results show that the integration of conductive yarn on fabric don’t reduce the fabric lifetime and moreover the sensing behaviour remains unalterable during the lifetime of the textile.
Keywords: smart-textile; sensor; textile; woven; abrasion; Martindale; inteligentna tkanina; czujnik; tekstylia; tkanie; przetarcie